PENGARUH PERUBAHAN FUNGSI PADA KEASLIAN BANGUNAN CAGAR BUDAYA DI BANDUNG STUDI KASUS : GEDUNG TIGAWARNA - Yulia B. Harahap; Alwin Saryono; Yuswadi Saliya (Riset Arsitektur (RISA), 2022)
Abstract - The development of the city of Bandung is very rapid with the emergence of modern buildings coloring the face of Bandung in almost all cities, this situation is caused by the increasingly diverse needs of the city, cultural heritage buildings are also affected, because their functions are changed according to the needs of their owners. There are many cultural heritage buildings whose functions have changed but do not pay attention to the authenticity of the buildings so that their condition becomes alarming, of the many cultural heritage buildings in Bandung, only a few of which are still visible in their authenticity even though their functions have changed. This study will raise the issue of the effect of changing functions on the authenticity of cultural heritage buildings with a focus on function and form, with the case study of Gedung Tiga Warna. This qualitative research puts forward a new way of reading that combines the Function-Form-Construction theory and the Preservation theory. The Tiga Warna Building, from the outside, still looks authentic, but many of the interior processing has changed from the original, due to the change in function from residential and office buildings to BTPN bank buildings. However, the original form is sought to be maintained, among others by using the same or similar materials as the original, both exterior and interior. The benefits of this research are expected to contribute to architectural knowledge for the community, input for academics and students of Architecture, as well as input for policy makers in formulating strategies for preserving cultural heritage buildings. Key words : Changes in function, authenticity, heritage building, Gedung Tigawarna.